The Impact of Gender, Nativeness, and Subject Matter on the English as a Second Language University Students’ Perception of Instructor Credibility and Engagement: A Qualitative Study - Rezvani, Reza; Miri, Parisa (Frontiers in Psychology, 2021)
In instructional contexts, instructor credibility or ethos is deemed to play a paramount role in teacher-student interaction and relationship. Much effort has been devoted to instructor credibility conceptualization, measurement, and its association with other instructional variables of interest in dominantly quantitative inquiries. However, little research has been undertaken in second language education in which communication is both a means and an end. This qualitative research set out to explore students’ perception of instructor credibility in the context of higher English education and how gender, nativeness and subject matter might impact their perception. It also aimed to study how instructor credibility could, in turn, influence students’ engagement and success. Thirteen senior students of English as a foreign language from a university in Iran participated in this study. They were given a scenario about their prospective professors for two courses of “Research Methodology” and “Essay Writing”. The professors included four native English- and Persian-speaking male and female Ph.D. holders. The participants were, then, interviewed about their perception of instructor credibility, their choice of instructors and how it would affect their engagement. The data were recorded, transcribed, and recursively analyzed using an inductive thematic analysis. While instructor credibility is commonly characterized as a three-dimensional construct involving competence, character, and caring, the data analysis generated a new component of performance concerned with the effectiveness of classroom knowledge presentation and activity organization. Caring also emerged as a constituent of a more inclusive component of rapport. Interestingly, albeit they viewed native English professors as generally more competent due to their nativeness, they perceived non-native professors as more credible for both courses mainly because of their rapport building and familiarity with students’ needs and challenges. Most of the participants also viewed male professors as more competent and communicative for both courses. The participants also tended to argue that perceived instructor credibility would encourage them to put in more efforts in their academic undertakings and to engage in class activities. This would ultimately enhance their academic achievements and success. The paper discusses the findings and implications for second language instructor credibility conceptualization and practice.